2018
DOI: 10.1353/hpu.2018.0029
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Retention Program to Improve Performance During the First Semester of a Doctor of Physical Therapy Program

Abstract: Implementation of a retention program had a beneficial effect on decreasing student dismissals in a physical therapy program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…On average, 25% to 37% of students responded that they had received tutoring (Garcia-Perez et al, 2021). The percentage of students seeking tutoring was found to be even less in DPT programs, reported as 21.7% (Owens et al, 2018).…”
Section: Academic Tutoringmentioning
confidence: 93%
See 1 more Smart Citation
“…On average, 25% to 37% of students responded that they had received tutoring (Garcia-Perez et al, 2021). The percentage of students seeking tutoring was found to be even less in DPT programs, reported as 21.7% (Owens et al, 2018).…”
Section: Academic Tutoringmentioning
confidence: 93%
“…The research on academic tutoring services has focused on improving academic performance as measured by grades, GPA, and program retention. The literature review revealed that 21.7% of DPT students seek academic tutoring services in DPT programs (Owens et al, 2018). In general, female students' participation in academic tutoring services is higher relative to male students (Garcia-Perez et al, 2021).…”
Section: Analysis Of the Findingsmentioning
confidence: 99%
“…While the SI programme is well-described in The Leader's Guide to Supplemental Instruction (The Curators of the University of Missouri, 2014), examples of SI organisation in pharmacy and nursing curriculum are lacking. Additionally, many interventions described as SI in the literature are modified, thus making it difficult to compare findings between studies Mosley, Maize, & LaGrange, 2013;Owens, Rainey, Tucker, & Edmunds, 2018). A special adaption of SI for this study involved sessions always being arranged by two SI leaders.…”
Section: Organisation Of the Si Programmementioning
confidence: 99%
“…As an educational model, SI is richly described in typical science courses (Hurley & Gilbert, 2008). Moreover, SI has also been implemented within health education -especially in anatomy and physiology courses (Bruno et al, 2016;Forester, Thomas, & McWhorter, 2004;Owens, Rainey, Tucker, & Edmunds, 2018). However, within pharmacy or nursing education, the literature on both the implementation and evaluation of SI remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of anatomy knowledge contributes to student performance and program attrition. Owens et al (2018) reported the benefits of supplemental instruction at their institute for students identified as at‐risk for receiving an unsatisfactory grade. Instruction that provides an integrating anatomy with patient experiences has shown the ability to improve program attrition (Raja et al, 2019).…”
Section: Introductionmentioning
confidence: 99%